Development of a train detection system and a spread spectrum transmission system for track circuit - Akio, T. (1997 IEEE 47th Vehicular Technology Conference. Technology in Motion, 2002)
Train safety is secured by the signalling system. The signal is transmitted to the train via rail track circuit. This transmission system is influenced by the train traction current in the rail. The track circuit transmission system of Shinkansen, the high speed train which operates at 275 km/h normally and at a maximum recorded speed of 440 km/h, adopts an SSB signal, which is synchronized with the power supply frequency, to avoid the influence of harmonic waves. This system has operated over 33 years without a fatal accident. Nevertheless the environment of the track circuit had become worse. The Central Japan Railway have undertaken basic experiments of a narrow band SS (spread spectrum) system which can endure a heavy noise environment. The experiments have been successful, and the theory and results are described.